2016
DOI: 10.4103/1305-7456.195160
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of platelet-rich fibrin versus beta-tri-calcium phosphate in the treatment of Grade II mandibular furcation defects using cone-beam computed tomography

Abstract: Objective:The objective of the study was to evaluate clinically and radiographically the efficacy of platelet-rich fibrin (PRF) versus β-tri-calcium phosphate (β-TCP) in the treatment of Grade II mandibular furcation defects.Materials and Methods:Forty-five Grade II furcation defect in mandibular molars which were assigned to open flap debridement (OFD) with PRF Group I (n = 15), to OFD with β-TCP Group II (n = 15), and to OFD alone Group III (n = 15) were analyzed for clinical parameters (probing pocket depth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 25 publications
3
24
0
Order By: Relevance
“…Seven abstracts were discarded due to the methodology not corresponding to the inclusion criteria; thus 15 full text papers were suitable for detailed examination; six articles were discarded according to the exclusion criteria after full text screening, and one article was excluded because some inconsistencies between the data reported in the tables and those reported in the text were found. In conclusion, eight studies were included in the systematic review [ 31 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seven abstracts were discarded due to the methodology not corresponding to the inclusion criteria; thus 15 full text papers were suitable for detailed examination; six articles were discarded according to the exclusion criteria after full text screening, and one article was excluded because some inconsistencies between the data reported in the tables and those reported in the text were found. In conclusion, eight studies were included in the systematic review [ 31 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…The studies were categorized based on the population characteristics as described in Table 2 , and on the clinical and laboratory parameters measured ( Table 3 ) and their findings. The PRF-centrifugation protocol was not homogeneous across the included studies and neither was the RCFmax (400× g for 10 [ 42 ] or 12 [ 45 , 47 ] minutes and 3000 rpm for 10 [ 31 , 43 , 46 , 48 ] or 12 [ 44 ] minutes). Non-standard types of centrifuges were used, and therefore the RCF was not comparable among them.…”
Section: Resultsmentioning
confidence: 99%
“…15 Other molecules, such as endothelial growth factors (including VEGF), act as avid stimulators of angiogenesis, thus increasing blood vessel synthesis. 12,45 Platelets and leukocytes are involved in VEGF expression; they are at their highest concentrations in the first hours after the clotting process, and VEGF levels gradually increase during the tissue healing process. 43 Rapid neovascularization is vital to tissue repair and regeneration, since angiogenesis enables the migration of tissue cells adjacent to the matrix, which, in turn, enables the repopulation of the injured area and the start of tissue repair.…”
Section: Molecular Parameters: Discussionmentioning
confidence: 99%
“…Results of the present study were in accordance with a study by Nagasri M et al, 2016 (21) who concluded that there were improvement on probing depth, Clinical attachment level and radiograghic bone fill when using NcHA bone graft +Platelet rich fibrin in intrabony defect, and a study by Enas ahmed et al (4) who concluded that Adjunctive use of PRF membrane in combination with NcHA bone graft in treatment of intrabony defect resulted in clinically, radiographically statistically significant compared with NcHA bone graft alone, in terms of PPD reduction, CAL gain and increase BD. In another study by Rahman Siddiqui et al 2016 (22) vertical and horizontal height of furcation was better when using PRF in treatment of class II furcation involvement.…”
Section: Discussionmentioning
confidence: 91%